Analisis Pengaruh Penggunaan Bahasa Campuran (Code-Mixing) dalam Pembelajaran IPA terhadap Kemampuan Menulis Teks Akademik Mahasiswa Pendidikan IPA Bilingual 2024 - Batubara, Astrida J.; Christy, Novia; Saragi, Shela Estica; Siregar, Suci Asda; Pasaribu, Tania; Lubis, Fitriani (Invention: Journal Research and Education Studies, 2025)
This study aims to analyze the effect of the use of mixed language (code-mixing) in Natural Sciences (IPA) learning on the ability to write academic texts of Bilingual Science Education students in 2024 in Medan State University. This study uses a quantitative method by distributing questionnaires to respondents. The research sample consisted of Bilingual Science Education students who took science courses. The results showed that the majority of respondents (around 54%) were neutral about the influence of the use of code-mixing in science learning on their ability to write academic texts. This indicates that the use of mixed languages does not have a significant impact, either positive or negative, on students' ability to write academic texts in the context of bilingual science learning. The implication of this study is the need for further research to explore other factors that may affect the academic text writing ability of bilingual students, as well as to identify alternative learning strategies that are more effective in improving students' academic text writing skills in the context of bilingual education.